Convergence of Monotone Generalized $α$-nonexpansive Mappings in Ordered Hyperbolic Metric Spaces - Samir Dashputre; Kavita Sakure (Sahand Communications in Mathematical Analysis)
In this paper, we discuss SPK iterative algorithm for approximating fixed point of monotone generalized $α$-nonexpansive mapping in the setting of partially ordered hyperbolic spaces. Indeed, we present some convergence results for the SPK iterative algorithm applied to monotone generalized $α$-nonexpansive mapping. Moreover, we provide an application of our results to nonlinear integral equations.